THE INFLUENCE OF REAL PROFIT AND CORPORATE GOVERNANCE MANAGEMENT AGAINST CREDIT RATING IN INDONESIA - Kusumawardhani, Indra; Windyastuti, Windyastuti; Susanto, Anindyo Aji (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2019)
This research investigated whether real earnings management and corporate governance affect the firm’s credit rating in Indonesia. Specifically, investigation on whether real earning management components, represented by AbnCFO, AbnDisExp and AbnPROD, together with corporate governance components, which are represented by board size, independent board and audit committee affect the firm’s credit rating. This research used several corporate governance mechanisms developed by Bursa Efek Indonesia and credit rating classification developed by PEFINDO. Multiple regression model is selected to test this research problem. This research found that AbnCFO and board size affected the firm’s credit rating, while AbnPROD, independent board and audit committee did not affect credit rating.